Pertumbuhan Anggrek Hitam (Coelogyne pandurata Lindl.) secara In Vitro Dengan Penambahan Ekstrak Tomat (Solanum lycopersicum L) Dan Benzyl Amino Purine (BAP) - Riza Linda, Serliana, Mukarlina, (Jurnal Protobiont, 2017)
Black orchid (Coelogyne pandurata Lindl.) Is an endemic germplasm Kalimantan. This orchid is in great demand because of the potential to have high economic value. Consequently, it is often overexploited, yet it has not been widely cultivated. This research aims to find out the effect of augmenting tomato extract and benzyl amino purine (BAP) in the growing of black orchid. This research started from January to March 2017 in Tissue Culture Laboratory Aloe Vera Center (AVC) Pontianak. This research used Completely Randomized Design (CRD) with 2 treatment factors and 3 repetition. The first factor was tomato extract (0%; 7,5%; 10%; 12,5%) and second factor was BAP (0 M; 10-6 M; 10-7 M). The results show that the single factor of tomato extract and BAP and the combination factor also did not have a real effect on the time shoots appear and the number of leaves. The interaction factor of tomato extract and BAP did not have a real effect on the number of shoots, but the single factor of tomato extract and BAP had a real effect on the number of shoots and single factor of BAP had a real effect on the number of leaves. The highest number of shoots was 3,33 in the treatment of tomato extract 7.5% and 1.33 in the treatment of BAP of 10-6 M. The highest number of leaves was 11.33 sheets in the treatment of tomato extract of 12,5% and the lowest number of leaves was in the treatment of tomato extract of 10% and BAP of 10-6 M with an average of 3,00 sheets.